Boris Paternak and the Tradition of German Romanticism - Evans-Romaine, Karen (Slavistische Beitraege, 1997)
The goal of this dissertation is to document Pasternak's reception of literature from three periods within German Romanticism: the early Romanticism of the Jena School's greatest literary representative, Friedrich von Hardenberg, whose pseudonym was Novalis; the "second-generation" Romanticism of E.T.A. Hoffmann; and the end and eventual rejection of German Romanticism, represented by Heinrich Heine. Revised version of the author's thesis (Ph. D.). University of Michigan, 1996. In kyrillischer Schrift